Wolność wypowiedzi a zjawisko manipulacji przekazem prasowym - Sobczak, Jacek (Przegląd Politologiczny, 2018)
The legal concept of human liberties and rights, including freedom of speech, is secondary to philosophical assumptions. Certainty of where the border between authority and freedom lies leaves the issue of the actual range of freedom unresolved. There is no, and there can be no absolute freedom, and the borders of every freedom are defined by legal regulations. This raises the question of whether a democratic state, a state of law, can make regulations in the realm of human rights and freedoms. In international relations, human rights are the foundation of all humanitarian law. There can be no violation of human rights in democratic states. The Constitution of Poland prioritizes human freedoms and rights in the constitutional hierarchy. Freedom of speech is placed particularly high in the hierarchy of liberties encompassed by human rights. Freedom of speech is guarded not only by Constitutional regulations but also detailed laws, which simultaneously establish the limits of the freedom of speech. These limits are also set by ethical norms. Journalists attempt to get around the legal limits that establish the framework of freedom and the barriers posed by codes of ethics, by means of manipulation of press releases. Manipulating society, journalists become a tool of authorities that are frequently not elected, not sovereign and are in fact acting on behalf of entities that remain anonymous and whose goals are undisclosed.